DETERMINACIÓN DE LA FACTIBILIDAD DEL DESARROLLO DE HERRAMIENTAS INFORMÁTICAS QUE PERMITAN UNA ADMINISTRACIÓN EFICIENTE DE LAS OPERACIONES DE TRANSPORTE Y DISTRIBUCIÓN DE MERCANCÍA EN EL MERCADO DE LAS PYME´S DE LA CIUDAD DE BARRANQUILLA (2014)
Overall logistics costs of a company in Colombia represent on average 22% of all commercial operation according to the ANDI (AsociaciónNacional de Industriales), hence, any effort to effectively manage the supply chain is valid only if one takes into account this percentage, especially for SMEs which do not have sufficient capital to invest in technology and software to carry out this operation with maximum performance. The project "determination of the feasibility of the development of tools that enable efficient management of the operations of transport and distribution of goods in the market of SMEs in the city of Barranquilla" aims to establish the feasibility of developing such tools and make them available to those companies who do not have enough for this type of investment. The research was developed in 4 major phases: first, determine the sample size where the population is declaratory to the last where an analysis of the feasibility for this kind of software is made. The study is extended to the companies that are part of the transport sector in Barranquilla, where a survey was developed about the shape and the resources currently used to manage transport and distribution operations of merchandise. Of the total number of companies, 70 were selected, which are companies dedicated to the freight transport and urban transport.